PENERAPAN CD PEMBELAJARAN IPA BERBASIS SIKLUS BELAJAR 5E TERHADAP KOMPETENSI PESERTA DIDIK KELAS VIII SMP NEGERI 2 PADANG - Mira Restuti; Festiyed Festiyed; Hidayati Hidayati (Universitas Negeri Padang, 2015)
This research described the applying of natural science learning CD which is based on the 5E learning cycles to overcome the problem about low of students’ competence achievement in learning natural science. This problem was caused by the limited materials and less interesting learning method used by the teachers so the students are lack of motivation to study and this situation drove to meaningless learning process. This research was Quasi-Experimental research and used Randomized Control Group Only Design. The population was VIII grade students in SMPN 2 Padang registered in 2014/2015 academic year. The samples were chosen by applying purposive sampling. There were two classes chosen as group samples; they are VIII3 class as experimental class and VIII2 class as control class. The data were collected and calculated statistically by using t-test in three domains equality test. The result of the research of three domains showed experimental class had higher average scores than control class. The result of statistical test showed that the differences of two classes had scores 0.05. It can be concluded that there is an effect on applying of natural science learning CD which is based on the 5E learning cycles